(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The paper examines an importance of AI and e-technologies and their key roles in such unexpected situation as COVID-19 and the emergence and progress of artificial generative technology. The authors propose diagnosis of Polish labor market which had to answer to both challenges of last years: technological and civilizations changes as well as post-pandemic time. The situation of currently required skills in Polish labor market under conditions of AI emergence and acceleration is treated as similar to circumstances in education, where one of the most needed skills became communication competences and dealing with IT, ICT, new media and AI technologies. The authors also raise a pivotal issue of new required skills and competences of coping with e-technologies: many jobs will be eliminated whilst others will be created. This means that future workers should be prepared to change their jobs and, perhaps, to work for more than one employer at the same time. The main method of research which is involved within the article is a desk research and review of the latest data and reports.